Aging Negatively Affects Estrogens-Mediated Effects on Nitric Oxide Bioavailability by Shifting ERα/ERβ Balance in Female Mice - Novensà, Laura; Novella, Susana; Medina, Pascual; Segarra, Gloria; Castillo, Nadia; Heras, Magda; Hermenegildo, Carlos; Dantas, Ana Paula (PLOS ONE, 2011)
Aims Aging is among the major causes for the lack of cardiovascular protection by estrogen (E2) during postmenopause. Our study aims to determine the mechanisms whereby aging changes E2 effects on nitric oxide (NO) production in a mouse model of accelerated senescence (SAM). Methods and Results Although we found no differences on NO production in females SAM prone (SAMP, aged) compared to SAM resistant (SAMR, young), by either DAF-2 fluorescence or plasmatic nitrite/nitrate (NO2/NO3), in both cases, E2 treatment increased NO production in SAMR but had no effect in SAMP. Those results are in agreement with changes of eNOS protein and gene expression. E2 up-regulated eNOS expression in SAMR but not in SAMP. E2 is also known to increase NO by decreasing its catabolism by superoxide anion (O2-). Interestingly, E2 treatment decreased O2− production in young females, while increased O2− in aged ones. Furthermore, we observed that aging changed expression ratio of estrogen receptors (ERβ/ERα) and levels of DNA methylation. Increased ratio ERβ/ERα in aged females is associated to a lack of estrogen modulation of NO production and with a reversal in its antioxidant effect to a pro-oxidant profile. Conclusions Together, our data suggest that aging has detrimental effects on E2-mediated benefits on NO bioavailability, partially by affecting the ability of E2 to induce up regulation of eNOS and decrease of O2−. These modifications may be associated to aging-mediated modifications on global DNA methylation status, but not to a specific methylation at 5′flanking region of ERα gene.